2012
DOI: 10.2478/v10006-012-0056-z
|View full text |Cite
|
Sign up to set email alerts
|

Joint queue-perturbed and weakly coupled power control for wireless backbone networks

Abstract: Wireless Backbone Networks (WBNs) equipped with Multi-Radio Multi-Channel (MRMC) configurations do experience power control problems such as the inter-channel and co-channel interference, high energy consumption at multiple queues and unscalable network connectivity. Such network problems can be conveniently modelled using the theory of queue perturbation in the multiple queue systems and also as a weak coupling in a multiple channel wireless network. Consequently, this paper proposes a queue perturbation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…The performance results agree with the theory that the offered load per link is directly proportional to the throughput in a lightly loaded network. The FIREMAN method was compared with the PSM-MMAC protocol in [5] and the SPWC-PMMUP in [14]. It has been found that the FIREMAN method for a three radio interface link outperforms the SPWC-PMMUP and PSM-MMAC methods tested under a similar number of the radio interfaces, on the average.…”
Section: Performance Evaluationmentioning
confidence: 97%
See 1 more Smart Citation
“…The performance results agree with the theory that the offered load per link is directly proportional to the throughput in a lightly loaded network. The FIREMAN method was compared with the PSM-MMAC protocol in [5] and the SPWC-PMMUP in [14]. It has been found that the FIREMAN method for a three radio interface link outperforms the SPWC-PMMUP and PSM-MMAC methods tested under a similar number of the radio interfaces, on the average.…”
Section: Performance Evaluationmentioning
confidence: 97%
“…The transmission energy adaptations were based on the locally residing energy in a node, the amount of local queue load, the quality of the links and the interference conditions in the wireless medium [13]. In [14], the inter-channel, co-channel interference, and energy consumption at the queues were modeled as joint queue-perturbation and weakly-coupled (SPWC) systems. A Markov chain model was developed to describe the steady state probability distribution behavior of the queue energy and buffer state variations in multi-radio nodes.…”
Section: Related Workmentioning
confidence: 99%
“…In [12], the inter-channel, co-channel interference and energy consumption at the queues were modelled as joint singular-perturbation and weakly-coupled (SPWC) systems.…”
Section: Related Workmentioning
confidence: 99%
“…On the other hand, if we deal with an inhomogeneous Markovian model, then we must approximately calculate, in addition to that, the limiting probability characteristics of the process. The problem of existence and construction of limiting characteristics for inhomogeneous (in time) birth and death processes is important for queueing applications (see, e.g., Di Crescenzo and Nobile, 1995;Di Crescenzo et al, 2003;Granovsky and Zeifman, 2004;Mandelbaum and Massey, 1995;Massey and Whitt, 1994;Massey and Pender, 2013;Olwal et al, 2012;Tan et al, 2013;Zeifman et al, 2006). This is the second main problem.…”
Section: Introductionmentioning
confidence: 99%